Identification of Evaluation Results in E-Banking Services Transaction for Product Recommendation using the BIRCH and Davies Bouldin Index Method - Buananta, Septian Eka Ady; Ahmad, Muhammad Aliif; Mahmood, Jamilah; Paradise, Paradise (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
E-banking transaction services in the banking world include many products offered to customers. However, the existence of regulatory factors may limit the extent to which banks can promote e-banking services, especially in cases where promotions involve incentives or special offers. Besides, there is a need for data analysis that is used to help the process of recommending product promos from these services. Recommendations for this product promo can be known from the evaluation process of data collected from e-banking transaction services for purchases and payments. The clustering method suitable for providing significant and influential results compared to other methods is BIRCH, which is assisted by the Davies Bouldin Index method to determine the list of product groups with the lowest value. The results of this evaluation process show that data can be grouped based on which services have low levels of use. The services in question are Deposits, Credit Cards on Mobile Services, OVB, and Inter-Bank Transfers on Mobile Services. Therefore, this service can be used as a reference to increase product promotion by the bank.